Flapping wing mechanism development and control / Nurasyeera Rohaizat - Nurasyeera , Rohaizat (2018)
Developing a dragonfly robot and reproducing the flapping mechanism involve challenging tasks particularly in terms of design and control to achieve high flapping frequency. Therefore, the purpose of this study is to develop a rigid flapping mechanism of a dragonfly robot. As such, the flapping mechanism of a dragonfly robot was modelled and a working prototype was then assembled. An open-loop control system of using an Arduino Uno microcontroller board was established with embedded radio frequency (RF) communication protocol to wirelessly control the robot from a personal computer. Moreover, an ultrasonic sensor was implemented as well for future development. Based on several experimental results, the developed flapping mechanism has worked reasonably well with the addition of greases on adjoining parts of the dragonfly robot. At 3V motor input voltage, the mechanism was able to produce a flapping frequency of 10Hz. On the other hand, the incorporation of an ultrasonic sensor offered an accuracy of up to 97.21%. when being tested with 3-15cm distances object. In conclusion, the work presented in this study serves as a basis understanding to develop an overall better flapping mechanism for a dragonfly robot in the future.